2022
DOI: 10.1177/15593258221113791
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effects of Apigenin Against Radiation‐Induced Intestinal Injury

Abstract: Radiation-induced intestinal injury (RIII) restricts the therapeutic efficacy of radiotherapy in abdominal or pelvic malignancies. Also, intestinal injury is a major cause of death following exposure to high doses of radiation in nuclear accidents. No safe and effective prophylactics or therapeutics for RIII are currently available. Here, we reported that the apigenin, a natural dietary flavone, prolonged the survival in c57 mice after lethal irradiation. Apigenin pretreatment brought about accelerated restora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Resveratrol was reported to modulate the activity of antioxidant enzymes to alleviate oxidative stress damage through the NRF2 signaling pathway in the livers of ducks, resulting from a lipopolysaccharide-induced inflammatory response [60]. One study showed that apigenin decreased irradiation-induced oxidative stress in mice by increasing NRF2 protein expression [61], while another demonstrated that apigenin promoted the nuclear translocation of NRF2 and enhanced the protein expression level of NRF2, in addition to the expression of the NRF2 target gene NQO-1 [62]. The ZO family of proteins are key components of tight junctions.…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol was reported to modulate the activity of antioxidant enzymes to alleviate oxidative stress damage through the NRF2 signaling pathway in the livers of ducks, resulting from a lipopolysaccharide-induced inflammatory response [60]. One study showed that apigenin decreased irradiation-induced oxidative stress in mice by increasing NRF2 protein expression [61], while another demonstrated that apigenin promoted the nuclear translocation of NRF2 and enhanced the protein expression level of NRF2, in addition to the expression of the NRF2 target gene NQO-1 [62]. The ZO family of proteins are key components of tight junctions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, CoAN is a crucial factor so that an agent can selectively kill tumor cells but with a protective effect on normal tissues. Interestingly, flavonoids have differential effects on normal and tumor tissues [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. For instance, Api has been associated with a reduced risk of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Table 3. 4 shows the binding energies and Ki of apigenin and related flavonoids with DNA gyrase B(PDB:6F86 and PDB:4PRV) and FABZ(PDB:3CF9 site A and site B). Our results show that apigenin and other flavonoids are capable of binding to DNA gyrase at both sites, but are more potent in binding to the PDB:4PRV site than PDB:6F86.…”
Section: Binding Energies and Inhibition Constants (Ki) Of Apigenin A...mentioning
confidence: 99%